2015
DOI: 10.15233/gfz.2015.32.9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of groundwater electrical conductivity using ordinary kriging and artificial intelligence methods (Case study: Tabriz plain, Iran)

Abstract: Artificial intelligence (AI) systems have opened a new horizon to analyze water engineering and environmental problems in recent decades. In this study performances of ordinary kriging (OK) as a linear geostatistical estimator and two intelligent methods including artificial neural networks (ANN) and adaptive neuro-fuzzy inference system (ANFIS) are investigated. For this purpose, geographical coordinates of 120 observation wells that located in Tabriz plain, north-west of Iran, were defined as inputs and grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…So, the common practice in the mentioned situations is to use mathematical, empirical or recently data-driven techniques, which have been established on the basis of measured meteorological parameters, to have precise estimations of actual solar radiation (Ozgoren, Bilgili, & Sahin, 2012;Sun, Zhao, Zeng, & Yan, 2015). Data-driven techniques have the numerous applications in hydrological engineering and contemporary real-life problems (Chau, 2017;Fotovatikhah et al, 2018;Jeihouni, Delirhasannia, Alavipanah, Shahabi, & Samadianfard, 2015;Moazenzadeh, Mohammadi, Shamshirband, & Chau, 2018;Samadianfard, Delirhasannia, Kisi, & Agirre-Basurko, 2013;Samadianfard, Nazemi, & Sadraddini, 2014;Samadianfard, Sattari, Kisi, & Kazemi, 2014;Taormina, Chau, & Sivakumar, 2015;Wu & Chau, 2011). So, the researchers attempt to develop accurate predictor models of solar radiation in various time scales that is a crucial issue of related solar energy sciences.…”
Section: Introductionmentioning
confidence: 99%
“…So, the common practice in the mentioned situations is to use mathematical, empirical or recently data-driven techniques, which have been established on the basis of measured meteorological parameters, to have precise estimations of actual solar radiation (Ozgoren, Bilgili, & Sahin, 2012;Sun, Zhao, Zeng, & Yan, 2015). Data-driven techniques have the numerous applications in hydrological engineering and contemporary real-life problems (Chau, 2017;Fotovatikhah et al, 2018;Jeihouni, Delirhasannia, Alavipanah, Shahabi, & Samadianfard, 2015;Moazenzadeh, Mohammadi, Shamshirband, & Chau, 2018;Samadianfard, Delirhasannia, Kisi, & Agirre-Basurko, 2013;Samadianfard, Nazemi, & Sadraddini, 2014;Samadianfard, Sattari, Kisi, & Kazemi, 2014;Taormina, Chau, & Sivakumar, 2015;Wu & Chau, 2011). So, the researchers attempt to develop accurate predictor models of solar radiation in various time scales that is a crucial issue of related solar energy sciences.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of ML models to model groundwater salinity has been demonstrated via the establishment of a linear or non-linear relationship between water salinity and its control parameters (such as water table, evaporation, and distance to saltwater bodies) and using those relationships for the prediction of water salinity for regions with unavailable data points 39 , 40 . Various versions of ML models have been reported in the literature, such as artificial neural network (ANN) 41 45 , support vector machine (SVM) 46 48 , adaptive neuro-fuzzy inference system (ANFIS) 49 , 50 , ensemble ML models 38 , 51 , 52 , group method of data handling (GMDH) 53 , and Gaussian process scheme 54 . The significant limitations associated with predictive ML models (1) the need for adequate input variables to explain the target data that may not be available everywhere 55 , 56 , (2) the influence of well excessive pumping 57 , 58 , (3) the reliability of the learning process of the predictive model where essential hyperparameters are optimized 59 , 60 , (4) coupled ML models where a pre-processing technique was integrated for data time series decomposition 61 , 62 .…”
Section: Introductionmentioning
confidence: 99%
“…Chowdhury et al [16] compared the ANN and ordinary kriging (OK) techniques for spatial estimation of the As concentrations in Bangladesh, and pointed out that a highly nonlinear pattern machine learning technique in the form of an ANN model can yield more accurate results than OK under the same set of constraints. Jeihouni et al [19] used the OK and two AI methods, namely, ANN and the adaptive neuro-fuzzy inference system (ANFIS), to spatially assess the electrical conductivity of groundwater. Their results indicated that ANFIS provides the best prediction accuracy with a root mean squared error (RMSE) value of 1.69 dS.m, whereas the RMSEs are 1.79 dS.m and 2.14 dS.m for ANN and OK, respectively.…”
Section: Introductionmentioning
confidence: 99%